The Media Banners and Leaflets on Stunting Prevention Counseling in Beringin Village - Rida' Millati; Rofi’atun Nur Ersanti; Maulana Akbar Stiraj Wibisono; Chandra Muhammad; Dhea Indah Cahyani; Khairunnida Khairunnida; Naela Sofa; Nor Aini Putri; Qois Dhya Wasimah Aqillah Dayaky Putri; Riani Riani; Widyani Widyani; Yuhda Fransisty (OMNICODE Journal (Omnicompetence Community Developement Journal), 2023)
The occurrence of stunting in Beringin Village, Alalak District, Barito Kuala Regency, has become a scourge for the Barito Kuala Health Service. Muhammadiyah University of Banjarmasin has an MoU with the Government of Barito Kuala Regency to work together to reduce stunting rates, play a role in increasing public knowledge and understanding. One of the activities is outreach and education/counseling on stunting prevention in the community. The main targets of the stunting reduction program this time are recitation mothers, teenagers, pregnant women, and mothers under two years old. The method used is counseling or conveying information about stunting with lectures and questions and answers. The procedure for preparatory activities is in the form of coordination with related parties in Beringin Village. Implementation in the form of counseling begins with apperception, then explanation of the material, questions and answers. Extension media used in the form of banners and leaflets. Evaluation procedure using the post test sheet. The evaluation results showed that 63.9% of residents had good knowledge about stunting. The conclusion is that there is a good understanding of the residents after being given counseling about stunting. Some of the obstacles that can be anticipated in future activities are wider venues, longer time, main activities, involving more religious leaders and community leaders when providing counseling